Atheist Critiques of the New Atheists: Advancing Atheist-Theist Dialogue Advancing Atheist-Theist Dialogue - Admirand, Peter (Interreligious studies and intercultural theology, 2020)
In this article, I examine atheist critiques of the New Atheists. The goals are both to highlight the diversity of atheist views and to examine how these intra-atheist dialogues and exchanges can advance atheist-theist dialogues and partnerships. As is commonly stressed, many New Atheist works tended to treat religion in a fairly provincial, negative way, leading many theists to claim their faiths were misrepresented or painted with an overly negative brush. Examining recent works of atheist thinkers like Michael Ruse, Philip Kitcher, Chris Stedman, and Timothy Crane presents atheist positions still critical of religious belief and arguments for God’s existence, but in a humble, open, non-judgmental, and reason-based approach. After examining a number of these works, the article concludes by highlighting seven features for viable and humbling atheist-theist dialogue for atheist participants. It also adds five lessons and examples theists can learn from this more conciliatory, dialogical approach.